2016
DOI: 10.1039/c6nj00430j
|View full text |Cite
|
Sign up to set email alerts
|

A Lawsone–DAMN based colorimetric chemosensor for rapid naked-eye detection of mercury(ii)

Abstract: We designed and synthesized a new colorimetric chemosensor L based on the combination of 3-hydroxy-1, 4-dioxo-1, 4dihydronaphthalene-2-carbaldehyde 2 and diaminomaleonitrile 3 moiety. The recognition abilities of the probe with a range of metal ions were evaluated and their optical properties have been systematically investigated. The chemosensor L exhibited well defined naked -eye visible color changes from yellow to pink for Hg 2+ in acetonitrile. Other ions, including Na + , Ca 2+ , CO 2+ , Ni 2+ , Cu 2+ , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…It has been used as the starting material for the synthesis of a variety of biologically active compounds and materials with interesting properties. [22][23][24][25] In recent decades, it has been used in many reactions for the synthesis of various organic compounds. 26 Moreover, synthesis of aminonaphthoquinone Mannich base derivatives, as an interesting class of naphthoquinones, by multicomponent reactions of lawsone with a non-enolizable aldehyde and a primary or secondary amine via the Mannich reaction and their metal complexes using different conditions, and applications of these compounds has been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used as the starting material for the synthesis of a variety of biologically active compounds and materials with interesting properties. [22][23][24][25] In recent decades, it has been used in many reactions for the synthesis of various organic compounds. 26 Moreover, synthesis of aminonaphthoquinone Mannich base derivatives, as an interesting class of naphthoquinones, by multicomponent reactions of lawsone with a non-enolizable aldehyde and a primary or secondary amine via the Mannich reaction and their metal complexes using different conditions, and applications of these compounds has been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…). By calculating from the gradient ( k = 3.36 × 10, R 2 = 0.995) and σ = 1.63 × 10 −3 , the detection limit was found to be 1.46 μmol L −1 (equal to 0.292 mg kg −1 ), which is comparable to those (0.11–4.6 μmol L −1 ) of other colorimetric chemosensors for Hg 2+ (Table ) and lower than the maximum allowable level of Hg 2+ for food and animal feed regulated by the US Food and Drug Administration (1 mg kg −1 ) . As shown in Fig.…”
Section: Resultsmentioning
confidence: 70%
“…The chemosensor (20) used in test strips was synthesized by the combination of diaminomaleonitrile and 3-hydroxy-1,4-dioxo-1,4- dihydronaphthalene-2-carbaldehyde. 55 The colorimetric sensing abilities of sensor (20) for Hg 2+ ion was again evaluated by UV-visible spectroscopy. It was observed that absorption bands of 20 at 335 nm and 481 nm were disappeared and new absorption bands at 421 nm and 595 nm were appeared on addition of Hg 2+ ion.…”
Section: Damn Based Chemosensors For Metal Ionsmentioning
confidence: 99%